Board representation in international joint ventures - Cuypers, Ilya R. P.; Ertug, Gokhan; Reuer, Jeffrey J.; Bensaou, Ben (Strategic Management Journal, 2017)
Research summary : Relatively little attention has been paid to boards in international joint ventures ( IJVs ), and the composition of these boards in particular. We examine the determinants of foreign partners' representation on IJV boards in order to advance our knowledge of this facet of IJV governance. We argue that a foreign partner's representation on the IJV board is related to its equity contribution. However, we hypothesize that this relationship is moderated by IJV and host country characteristics that affect the importance of the internal and external roles IJV boards serve. These results provide insights into the conditions under which a partner might wish to secure greater board representation for its level of equity, or utilize less board representation than might be suggested by its equity level alone . Managerial summary : The functioning and composition of corporate boards have long been seen as critical to managers and shareholders alike. In contrast, the boards of IJVs have been relatively neglected. We advance our knowledge of this important facet of IJV governance. Specifically, we highlight the importance of two roles (i.e., an internal and external role) that IJV boards and directors fulfill. We find that the importance of these internal and external roles of boards determines whether a foreign partner might wish to secure greater board representation for its level of equity, or utilize less board representation than might be suggested by its equity level alone. Our results provide novel insights that can help managers structure their IJV boards . Copyright © 2016 John Wiley & Sons, Ltd.